Linearity in functional sentence perspective: the strength of the weak factor - Vladislav Smolka (Linguistica Pragensia, 2015)
When the theory of Functional Sentence Perspective (FSP) is applied to English, the linear arrangement of clause constituents is considered the weakest of the four factors indicating the distribution of communicative dynamism over a sentence, following the contextual factor, the semantic factor and, in spoken language, the prosodic prominence. The relative weakness of linearity as an FSP factor results from the limited positional mobility of clause constituents in English, where the position of an element in the sentence primarily indicates its syntactic function. However, the linear distribution of clause constituents may sometimes override the other factors and become the principal indicator of FSP. In such cases, the importance of linearity is signalled by the choice of an arrangement that is normally dispreferred because it conflicts with the usual wordorder principles. These deviations from the usual word order include, for example, movement of a constituent from its usual position and instances of flouting the principle of end-weight. This paper explores the range of structures where linearity overrides the other FSP factors and the conditions under which it can assert itself as the leading indicator of FSP.